When treating canine diabetic ketoacidosis, do balanced crystalloids provide superior outcomes compared to 0.9% Saline? - Marella, Sara (Veterinary Evidence, 2022)
PICO question When treating canine diabetic ketoacidosis, do balanced crystalloids provide superior outcomes compared to 0.9% saline? Clinical bottom line Category of research question Treatment and prognosis The number and type of study designs reviewed Zero Strength of evidence Zero Outcomes reported There is currently a lack of studies looking at comparing 0.9% saline to a buffered crystalloid solution (such as Hartmann's) in dogs with diabetic ketoacidosis Conclusion In view of the strength of evidence and the outcomes from the analysed studies, there is currently no evidence that the use of 0.9% saline or the use of a buffered crystalloid affects the outcome in dogs with diabetic ketoacidosis How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.